Descolonização - Vera Lucia Amaral Ferlini (Revista de História, 1977)
SANTHIAGO, Theo (Org.). Descolonização. Trad. Antônio Monteiro Guimarães Filho, Theo Santhiago e José Fernandes Dias. Rio de Janeiro: Francisco Alves, 1977, 200 pp.